Narrow [O iii] Emission Lines as a Potential Proxy for the Evolutionary Stage of Quasars - Zhi-fu Chen; Zhe-Geng Chen; Xing-long Peng; Wei-rong Huang (The Astrophysical Journal)
Radio spectral shape of quasars can provide insight into the ages of quasars. We have compiled data for 1804 quasars with z ≲ 1 from the Sloan Digital Sky Survey (SDSS). Additionally, these quasars were also mapped by the Low-Frequency Array at 144 MHz and the Very Large Array Sky Survey at 3000 MHz. The radio spectral index, designated as ${α }_{3000}^{144}$ (with S ( ν ) ∝ ν ^α ), is analyzed between 144 and 3000 MHz as a proxy for the ages of quasars. We measure the [O III ] λ 5007 emission line in the SDSS spectra. A strong correlation was found between the equivalent width of the core component of the [O III ] λ 5007 emission line and ${α }_{3000}^{144}$ . This relationship suggests that the core component of the [O III ] λ 5007 emission line could potentially serve as a surrogate for the evolutionary stage of a quasar. The quasars at an early stage of evolutions tend to show weaker [O III ] λ 5007 emission, while older quasars exhibit stronger [O III ] λ 5007 emission.